Is Myocarditis an Independent Risk Factor for Post-Transplant Mortality in Pediatric Heart Transplant Recipients?. (January 2016) - Garbern, Jessica C.; Gauvreau, Kimberlee; Blume, Elizabeth D.; Singh, Tajinder P.
Abstract : Background—: Previous studies suggest that children with myocarditis who receive heart transplantation (HT) may be at higher risk of post-transplant mortality compared with children who are transplanted for idiopathic dilated cardiomyopathy. We hypothesized that these differences are because of more severe heart failure at HT in children with myocarditis. Methods and Results—: We identified 221 children with myocarditis and 1583 with idiopathic dilated cardiomyopathy who were <18 years old and listed for HT in the United States between July 2004 and December 2013 using the Organ Procurement and Transplant Network database. We compared baseline characteristics at listing and at HT and used Cox models to determine whether myocarditis is independently associated with wait-list mortality (or becoming too sick to transplant) or post-transplant graft loss (death/re-HT). Children with myocarditis were more likely to be listed while on assisted ventilation, mechanical circulatory support and with renal dysfunction. Overall, 137 children with myocarditis and 1249 with idiopathic dilated cardiomyopathy received HT. In unadjusted analysis, children with myocarditis were at higher risk of wait-list mortality (hazard ratio 2.1; 95% confidence interval 1.5–3.0) and showed a trend toward increased risk of post-transplant graft loss (hazard ratio 1.4; 95% confidence interval 1.0–2.2). However, in adjusted analysis, myocarditis was not associated with wait-list mortality (hazard ratio 1.3, 95% confidence interval 0.9–1.9) or post-transplant graft loss (hazard ratio 1.3, 95% confidence interval 0.9–2.0). Conclusions—: Among children listed for HT, those with myocarditis have more severe heart failure than children with idiopathic dilated cardiomyopathy. After adjustment for severity of illness, myocarditis does not confer additional risk for wait-list or post-transplant mortality. Abstract : Supplemental Digital Content is available in the text.